(untitled) (Al-Academy, 2019)
The sound in the cinema and television occupies a large space in the level of use and expression. In addition to the functional aspect of the elements of the sound such as the dialogue, music, effects and silence, in shaping and supporting the narrative structure of the image in the dramatic work, it has today become and in light of the technical developments of the sound, an aesthetic value in the structure and formulation of the contents and ideas presented in the work. The sound also created a variety of forms before the work-factories in the artistic functioning, which enhances the emotional and expressive dimension of the image, and the researcher, as a result of many new developments in the expression of sound in Cinematography discourse, chose the subject of his research under the titled "The aesthetics of the use of sound in Cinematography discourse", and divided his work into the methodological framework and theoretical framework: The research was divided into two sections: the first one (the elements of sound in the Cinematography discourse), and the second section (the aesthetics of sound use in the cinematographic discourse). This section was concluded with the indicators, and the research procedures. The researcher tackled the research methodology and tools as well as the analysis unit and the research sample added to that the analysis of the sample based on the indicators and then the most important results reached at were: the sound is use not only to highlight the features of time and place, but to the aesthetic use of the elements of sound and to highlight and convince with the dramatic actions taken by the interaction within time and place. The research ended with the conclusions and a list of sources.